A escolha do gestual e suas implicações interpretativas aplicadas à regência da obra Psalmus, de João Guilherme Ripper - Araújo, Katarine de Sousa (2014)
This aim of this paper is to study and apply gestures in the interpretation of the symphonic work Psalmus, by João Guilherme Ripper. Zagonel (1992) and Heller (2006), were the references used in defining gesture. To define interpretation, the author consulted Laboissiére (2007), Lima (2006) and Schuller (1997), and for the definition of style and conducting, the author makes reference to Schuller (1997) and Swarowsky (1989). Once the definitions were established, the next step was to choose a representative contemporary work, in this case, the symphonic piece Psalmus (2002), by João Guilherme Ripper, from the Brazilian symphonic literature. The choice of this work was based on the following criteria: it is a contemporary Brazilian 21st Century piece, and while it presents technical and interpretation challenges to the conductor, it is not excessively complex for young musicians. This piece was played by the Orquestra Sinfônica Jovem de Goiás, rehearsed and conducted by the author of this paper. The data collected by this survey were approached and discussed with a view to their qualitative aspects. Musical elements are employed as guide to this study. For that purpose, rehearsals were recorded and the resulting video and audio focused on the conductor. Results point to the challenge of conciliating the conductor’s gestures, as a means to establish and maintain the beat while, at the same time, bringing the work to life. Additionally, an analysis of the results indicates that since this is a contemporary Brazilian work, it also presents a challenge to conducting students and these difficulties must be approached throughout their training.